Association between Access to Clean Water and Health Services and the Incidence of Stunting in Sungai Landas Village, Banjar District, South Kalimantan - Rahma, Amelia; Khadafi, Muhammad Zainal; Nayla, Nurul Alifa; Azmiyannoor, Muhammad; Rahman, Fauzie; Arifa, Salsabila; Setiawan, Muhammad Irwan; Sai'dah, Habibah (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2025)
Stunting among infants and toddlers in Sungai Landas Village, Banjar Regency, remains above the national target. Access to clean water and healthcare services plays a crucial role in preventing stunting, but the relationship between these two factors in this area has not yet been studied simultaneously. The study aim to analyze the association between access to clean water and access to healthcare services with the incidence of stunting among children under five in Sungai Landas Village. A quantitative cross-sectional study was conducted involving 30 children under five selected through purposive sampling. Data were obtained using an adapted Indonesian Nutritional Status Survey (SSGI) questionnaire, which assessed water source quality and the frequency of access to healthcare services. Stunting status was determined by measuring height-for-age according to Regulation of the Minister of Health No. 2 of 2020. Bivariate analysis was run with Fisher’s Exact test to assess the association between access to clean water and healthcare services and stunting incidence. Bivariate analysis revealed no significant association between access to clean water and stunting (p = 0.267), nor between access to healthcare services and stunting (p = 0.469). There is no significant association between the type of drinking water source or the frequency of healthcare service access and stunting among children under five in Sungai Landas Village. Other factors, such as a balanced diet and hygienic practices, also play a role. Recommendations include strengthening education on water treatment and family nutrition, improving the quality of healthcare services, and implementing multisectoral programs for more effective stunting reduction.